MANFAAT PENERAPAN CARBON ACCOUNTING DI INDONESIA - Dwijayanti, S. Patricia Febrina (Jurnal Akuntansi Kontemporer, 2011)
Carbon accounting is a process or a way to measure carbon emissions, then set a strategy to reduce carbon emissions, recording costs incurred and reported to the stakeholders of the company. The application of carbon accounting is a good benefit for a country, including Indonesia. For companies, the application of carbon accounting could be part of Corporate Social Responsibility (CSR) and will bring a positive impact for the company. For the government of Indonesia, carbon accounting can push the path of cooperation with countries associated with REDD (Reducing Emissions from Deforestation and forest Degradation), to reduce Greenhouse Gas (GHG) emissions. Indonesian society also have benefitfrom the application of carbon accounting. If the industry implementing carbon accollnting to reduce carbon emissions, so air pollution will be reduced and public !1ealth in the industry area will also be. improved. Application of carbon accounting could also reduce the potential natural disasters, the development of new infrastructure throughfundingfrom the REDD partnership and it will appear new jobs.